(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Tongue twisters have been a subject of interest in linguistics due to their complex phonetic structure and their cognitive effects on language processing. These verbal challenges, often characterized by rapid repetition of similar sounds or words, offer insights into speech production, phonological awareness, and motor coordination. This article provides an overview of the role of tongue twisters in linguistics, exploring their use in phonetics, language acquisition, and cognitive linguistics. Additionally, it examines how tongue twisters are utilized as tools in language teaching and their potential benefits in improving fluency and pronunciation. The article also considers the cultural significance of tongue twisters in various languages, focusing on the English and Uzbek languages.